Combining chemotherapeutic agents and netrin‐1 interference potentiates cancer cell death. Issue 12 (8th October 2013) - Paradisi, Andrea; Creveaux, Marion; Gibert, Benjamin; Devailly, Guillaume; Redoulez, Emeline; Neves, David; Cleyssac, Elsa; Treilleux, Isabelle; Klein, Christian; Niederfellner, Gerhard; Cassier, Philippe A.; Bernet, Agnès; et al.
<x xml:space="preserve">Abstract</x> The secreted factor netrin‐1 is upregulated in a fraction of human cancers as a mechanism to block apoptosis induced by netrin‐1 dependence receptors DCC and UNC5H. Targeted therapies aiming to trigger tumour cell death via netrin‐1/receptors interaction interference are under preclinical evaluation. We show here that Doxorubicin, 5‐Fluorouracil, Paclitaxel and Cisplatin treatments trigger, in various human cancer cell lines, an increase of netrin‐1 expression which is accompanied by netrin‐1 receptors increase. This netrin‐1 upregulation which appears to be p53‐dependent is a survival mechanism as netrin‐1 silencing by siRNA is associated with a potentiation of cancer cell death upon Doxorubicin treatment. We show that candidate drugs interfering with netrin‐1/netrin‐1 receptors interactions potentiate Doxorubicin, Cisplatin or 5‐Fluorouracil‐induced cancer cell death in vitro. Moreover, in a model of xenografted nude mice, we show that systemic Doxorubicin treatment triggers netrin‐1 upregulation in the tumour but not in normal organs, enhancing and prolonging tumour growth inhibiting effect of a netrin‐1 interfering drug. Together these data suggest that combining conventional chemotherapies with netrin‐1 interference could be a promising therapeutic approach.